2012
DOI: 10.1007/s00428-012-1225-z
|View full text |Cite
|
Sign up to set email alerts
|

Nonsebaceous lymphadenoma of salivary glands: proposed development from intraparotid lymph nodes and risk of misdiagnosis

Abstract: Nonsebaceous lymphadenoma (NSLA) is a rare benign salivary gland tumor composed of lymphoid and epithelial components. By definition, the epithelial component lacks sebaceous differentiation and instead displays a wide range of histological differentiation. In this study, we have collected nine cases of NSLA to characterize their histological and immunohistochemical profiles. The samples were histologically reviewed and immunohistochemical stains for CK5/6, CK7, CK14, CK18, p63, and Ki67 performed. Patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 20 publications
0
25
3
Order By: Relevance
“…In the present study, this type of tumor was observed to be well circumscribed and exhibited typically benign behaviors, with the majority of the cases affecting adults aged >30 years (80%). Of the 10 cases, approximately one-third exhibited sebaceous differentiation to an extent, which was the opposite to the findings of a previous study (3). The underlying specific reasons for this phenomenon are not yet clear.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…In the present study, this type of tumor was observed to be well circumscribed and exhibited typically benign behaviors, with the majority of the cases affecting adults aged >30 years (80%). Of the 10 cases, approximately one-third exhibited sebaceous differentiation to an extent, which was the opposite to the findings of a previous study (3). The underlying specific reasons for this phenomenon are not yet clear.…”
Section: Discussioncontrasting
confidence: 91%
“…A strong argument for this hypothesis are that studies have identified an unequivocal hilus structure with embryonic parenchymal inclusions, in conjunction with frequent secondary follicles and lymph vessels within the marginal sinus structures (2,3,7,10). However, this theory is in conflict with the majority of studies, which instead regard the lymphoid component as reactive tumor-associated lymphoid tissue (6,8,1113).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 2005 World Health Organization Classification of Tumors, NSL is classified as a subtype of lymphadenoma, together with sebaceous lymphadenoma . Since 1991, to the best of our knowledge, only 37 cases of NSL have been reported in the literature, and none of the reported tumors showed the differentiation to serous acinic cell lineage. Here, we present for the first time a case of NSL of the parotid gland with serous acinic cell differentiation.…”
mentioning
confidence: 99%
“…Some may have argued that lymphadenoma may represent an adenoma arising from heterotopic salivary tissue in an intra-or periparotid lymph nodes. Hilus structure with salivary inclusions or D2-40 (podoplanin)-positive marginal sinus was identifi ed in four and nine of their nine cases, respectively [ 168 ]. On the other hand, others have not demonstrated recognisable lymph node structures with sinuses, and furthermore, the lymphoid component is by many considered to represent tumour-associated lymphoid proliferation [ 7 , 41 ].…”
Section: Lymphadenomamentioning
confidence: 99%